A study on the correlation between vaginal conductivity and estrus in Hanwoo ( Bos taurus coreanae ) cows - Yi, Junkoo; Park, Jinyeon; Ha, Jaejung; Yu, Daejung; Kwon, Woo-Sung; Kim, Daehyun (Journal of animal reproduction & biotechnology (Online), 2023)
Background: Estrus in cows can be detected through vaginal electrical resistance or conductivity. However, there are no studies measuring vaginal electrical resistance in Hanwoo cows. This study aims to measure the vaginal electrical resistance value in Hanwoo cows and compare it with estrus and ovulation. Methods: Vaginal electrical resistance values of 73 Hanwoo cows were measured before and after estrus at the Gyeongsangbuk-do Livestock Research Institute. Measurements were taken on days -6, -3, -2, -1, 0, 1, 2, 3, and 6 of artificial insemination. Large follicles and ovulation were confirmed using transvaginal ultrasonography. Results: The vaginal electrical resistance averaged 225.6 ± 6.3 Ω days before the artificial insemination date, decreasing until the day of artificial insemination. The average vaginal electrical resistance was 163.7 ± 4.6 Ω on the date of artificial insemination, and 188.8 ± 4.3 Ω one day after artificial insemination, when large follicles were observed. In addition, on the 6th day after artificial insemination, the vaginal electrical resistance averaged 231.4 ± 5.5, which was similar to the 6th day before artificial insemination (222.5 ± 6.3). Transvaginal ultrasonography showed that most of the cows ovulated one day after artificial insemination. Conclusions: The accuracy of estrus is high if the vaginal electrical resistance is measured for cows with confirmed estrus, making is a potentially useful for determining the timing of artificial insemination.